Identifying the optimal harvest stage for forage and biogas production from sweet sorghum under semi-arid Mediterranean conditions - Recep Irfan Nazli; Burak Beyaz; Asiye Sena Cavdar; Hasan Beytullah Donmez; Muhammad Azhar Nadeem (Biomass and Bioenergy, 2027)

Genetic Diversity and Population Structure of 72 Turkish Ficus carica (L.) Genotypes Assessed Using SCoT Markers - Meliha Feryal Sarıkaya; Muhammad Azhar Nadeem; Sarmad Ali Qureshi; Mehmet Bedir; Muhammed Tatar; Amjad Ali; Muhammad Tanveer Altaf; Viyan Acar Uçer; Kağan Kökten; Erdal Aglar; Faheem Shehzad Baloch (Biochemical Genetics, 2026)

Charcoal rot in sesame: infection biology, host resistance mechanism, and genomic-enabled strategies for durable resistance breeding - Amjad Ali; Muhammad Azhar Nadeem; Fatih Ölmez; Cemal Kurt; Faheem Shehzad Baloch (Theoretical and Applied Genetics, 2026)
Sesame ( Sesamum indicum L.) is a globally important oilseed crop, but its production is constrained by charcoal rot, caused by the soil-borne fungus Macrophomina phaseolina. The pathogen’s exceptionally broad host range, long-term soil persistence through microsclerotia, and increased aggressiveness under high temperature and drought make charcoal rot a major destructive constraint in sesame-growing regions. This review integrates current knowledge on the biology, epidemiology, infection processes, and genetic population variability of Macrophomina spp. in relation to charcoal rot development in sesame. We also summarize key host resistance mechanism including pathogen perception, cell wall reinforcement, phenylpropanoid-mediated defense, antioxidant responses, and associated physiological and molecular adaptations. Particular attention is given to the challenges of resistance screening under variable environmental conditions, including heat- and drought-associated disease expression and pathogen diversity, which complicate the identification of stable resistance sources. The review further examines progress in sesame improvement through germplasm characterization, mutation breeding, interspecific introgression, high-throughput phenotyping, and genomic-assisted approaches such as QTL mapping, genome-wide association studies (GWAS), marker-assisted selection, genomic selection, and functional validation. Integrating these tools with multi-omics and gene-editing strategies offers a promising route for accelerating the development of durable, climate-resilient charcoal rot resistance cultivars. Broader use of diverse germplasm, standardized multi-environment phenotyping, and international collaboration will be essential for sustainable resistance breeding and future sesame production.

Enhanced charge carrier separation in greenly synthesized ZnO-NiO NCs-based Z-scheme heterojunction for photodegradation of ciprofloxacin hydrochloride and hydrogen evolution reaction - Abu Bakar Siddique; Muhammad Ashraf Shaheen; Azhar Abbas; Shoaib Akhtar; Muhammad Shahzad; Akbar Ali; Nadeem Ahmad; Hatem A. Abuelizz; Rashad Al-Salahi (Fuel, 2026)

Unveiling genetic diversity and population structure in lentil (Lens culinaris) germplasm through scot markers - Sarmad Ali Qureshi; Muhammad Azhar Nadeem; Meliha Feryal Sarıkaya; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altafl; Dilek Tekdal; Muhammad Kashif Ilyas; Seyithan Seydoşoğşu; Sezai Ercişli; Kağan Kökten; Faheem Shahzad Baloch (Molecular Biology Reports, 2025)

Molecular screening of stripe rust and powdery mildew resistance genes in European bread wheat using the validated gene-specific SSR markers - Rada Šućur; Amjad Ali; Parnaz Mortazavi; Velimir Mladenov; Bojan Jocković; Jin Ying Gou; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Yong Suk Chung (Physiological and Molecular Plant Pathology, 2025)

Exploring genetic diversity of Turkish fig (Ficus carica L.) germplasm using inter-Primer Binding Site (iPBS) retrotransposon markers - Viyan Acar Uçer; Erdal Aglar; Parnaz Mortazavi; Sarmad Ali Qureshi; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altaf; Mehmet Bedir; Sezai Ercişli; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Mineral profiling of Turkish wheat genetic resources unveiled their conserved potential for biofortification in combating hidden hunger - Husnu Aktaş; Muhammad Azhar Nadeem; Yusuf Tutuş; Serap Doğan; Mehmet Karaman; İrfan Erdemci; Meng-Lu Wang; Jin-Ying Gou; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Molecular screening of diverse Tomato germplasm for root-knot nematode resistance using the Mi23 marker - Parnaz Mortazavi; Amjad Ali; Muhammed Tatar; Fatih Ölmez; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Hayriye Yildiz Dasgan; Boran Ikiz; Tuğçe Temtek; Ömer Faruk Bilgin; Ayşe Mücahitoğlu; Mahmut Bayram; et al. (Physiological and Molecular Plant Pathology, 2025)

Molecular diversity and phylogenetic analysis of ten sheep breeds from Khyber Pakhtunkhwa, Pakistan, based on mitochondrial D-loop sequences - Shabir Ahmed; Muhammad Shahid Nadeem; Anna M. Johansson; Elisabeth Jonas; Khushi Muhammad; Sardar Azhar Mehmood (Mammalian Genome, 2025)

Development of tetraploids in tissue culture: modern techniques and biotechnological innovations - Sabeen Rehman Soomro; Salma Naimatullha Soomro; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Muhammad Aasim; Heba I. Mohamed (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Applicability of Start Codon Targeted (SCoT) markers for the assessment of genetic diversity in bread wheat germplasm - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Waqas Liaqat; Mehmet Bedir; Nurettin Baran; Aleksandra Ilić; Muhammad Kashif Ilyas; Abdul Ghafoor; Hamide Dogan; Muhammad Aasim; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)
Research endeavors focused on examining genetic diversity play a pivotal role in advancing agricultural practices, as they furnish valuable insights for breeding programs and the preservation of germplasm. Wheat holds significant global importance as a cereal crop, serving as a primary source of sustenance for almost one-third of the global human population. In the current study, a total of 80 bread wheat genotypes were characterized using the start codon targeted (SCoT) marker system. A set of 14 polymorphic primers yielded a cumulative count of 399 bands with an average of 28.05 bands per primer. The range of diversity markers, such as polymorphism information content (0.26–0.59), effective numbers of alleles (1.27–1.59), Shannon’s information index (0.30–0.51), and gene diversity (0.18–0.34), provided evidence of elevated genetic differences within the examined germplasm. According to the findings of the molecular variance analysis, greater genetic variations are found within populations (92%). The model-based structural approach partitioned the 80 bread wheat genotypes into two distinct populations (Population A and B). The diversity indices based on the structures of the populations revealed that population A had greater diversity compared to population B. Both the principal coordinate analysis and the neighbor-joining analysis also differentiated the 80 different bread wheat genotypes based on their respective collection points. The present crop diversity offers great opportunities for enhancing crop quality and increasing tolerance to environmental challenges, both of which will lead to a reduction in the problem of food insecurity.

Suppression of canary grass (Phalaris minor) with simultaneous use of rhizobacteria and sunflower allelopathy - Abubakar Dar; Umme Habiba; Muhammad Tauseef Jaffar; Maqshoof Ahmad; Azhar Hussain; Umar Farooq; Sajid Mehmood Nadeem; Muhammad Zahid Mumtaz; Usman Zulfiqar; Abd El-Zaher M.A. Mustafa; Mohamed S. Elshikh (Rhizosphere, 2024)

Applicability of SCoT markers in unraveling genetic variation and population structure among sugar beet (Beta vulgaris L.) germplasm - Nazlı Aybar Yalinkiliç; Sema Başbağ; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Molecular Biology Reports, 2024)

Strategies and bibliometric analysis of legumes biofortification to address malnutrition - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Celaleddin Barutçular; Muhammad Azhar Nadeem; Heba I. Mohamed (Planta, 2024)

Investigation of genetic diversity among autochthonous grape cultivars grown in Türkiye using molecular primers - Ahmet Sümbül; Ercan Yildiz; Ali Sabir; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2024)
Grape is a type of fruit widely grown globally and in Türkiye thanks to its importance in human nutrition and diversity of usage areas. Türkiye has a long history of grape cultivation, and the genetic diversity of local grapes grown in some regions has still not been revealed. This study showed the genetic diversity between 60 local grape genotypes selected from north Central Anatolia and nine reference grape cultivars;10 inter simple sequence repeats (ISSR) and 7 inter-primer binding site (IPBS) retrotransposon primers were used. The mean values of genetic diversity indices in ISSR and IPBS retrotransposon primers were calculated as expected allelic frequency (p) 0.476/0.195, observed allelic frequency (q) 0.524/0.805, number of effective alleles (Ne) 1.326/1.378, Shannon’s information index (I) 0.308/0.367, expected heterozygosity (He) 0.199/0.232 and unbiased expected heterozygosity (uHe) 0.201/0.234, respectively. Unweighted pair group method with arithmetic mean (UPGMA) and model-based STRUCTURE analysis divided the studied germplasm into two groups. However, local genotypes were not grouped per the regions where they grew. As a result of the analysis of molecular variance (AMOVA) analysis, the inter-population variation was determined to be 11%, and the intra-population variation was determined to be 89%. The mean genetic differentiation value (Fst) between populations was 0.303. The results showed that ISSR and IPBS retrotransposon primers effectively explained the genetic diversity.

Frontiers in bacterial-based green synthesized nanoparticles (NPs): A sustainable strategy for combating infectious plant pathogens - Amjad Ali; Muhammad Aasim; Kübra Çelik; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Biocatalysis and Agricultural Biotechnology, 2024)

Stripe rust resistance gene Yr15 in Turkish and Kazakhstan wheat germplasms and the potential of Turkish wild emmer for stripe rust breeding - Faheem Shehzad Baloch; Amjad Ali; Daniyar Tajibayev; Muhammad Azhar Nadeem; Fatih Ölmez; Hüsnü Aktaş; Ahmad Alsaleh; Gönül Cömertpay; Mustafa Imren; Zemran Mustafa; Abdelfattah A. Dababat; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2024)

Assessment of molecular and metabolic traits of a newly isolated Spirulina platensis BERC15 in a low-cost cultivation alternative for its use as functional food - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Adnan Ul Haq; Ayesha Shahid; Sana Malik; Amna Jabbar Siddiqui; Ning Wang; Hui Zhu; Azhar Rasul; Ahmed Hassan Chaudhry; Khalid Nadeem; Raj Boopathy; et al. (Bioresource Technology Reports, 2024)

Elucidating the genetic diversity and population structure of international cotton germplasm using inter-primer binding site (iPBS) retrotransposon marker system - Binnur Yeşil Bayrıl; Allah Bakhsh; Muhammad Azhar Nadeem; Ufuk Demirel (Genetic Resources and Crop Evolution, 2024)

Artificial intelligence models for validating and predicting the impact of chemical priming of hydrogen peroxide (H2O2) and light emitting diodes on in vitro grown industrial hemp (Cannabis sativa L.) - Muhammad Aasim; Buşra Yıldırım; Ahmet Say; Seyid Amjad Ali; Selim Aytaç; Muhammad Azhar Nadeem (Plant Molecular Biology, 2024)

Remediation of organic pollutant from the aqueous environment using in-house fabricated polyaniline-based hybrid composite (PANI-MnPBA/NiCoMnS) materials - Naseem Ahmad Khan; Muhammad Imran; Muhammad Nadeem Akhtar; Shabbir Hussain; Muhammad Azhar Khan; Ashwag Shami; Hafiz Iqbal (Chemosphere, 2024)

Genome-wide association studies revealed DArTseq loci associated with agronomic traits in Turkish faba bean germplasm - Tolga Karaköy; Faruk Toklu; Eylem Tuğay Karagöl; Damla Uncuer; Yeter Çilesiz; Amjad Ali; Muhammad Azhar Nadeem; Hakan Özkan (Genetic Resources and Crop Evolution, 2024)

Genetic characterization of coarse and basmati rice (Oryza sativa L.) through microsatellite markers and morpho-agronomic traits - Tahira Luqman; Zia-ul Qamar; Aqsa Tabasum; Wael. H. El-Kallawy; Talha Nazir; Safira Attacha; Sajid Fiaz; Muhammad Azhar Nadeem; Amjad Hameed; Zahra Maryum; Itoh Kimiko; Kotb Attia (Genetic Resources and Crop Evolution, 2023)

iPBS-retrotransposons variations: DNA fingerprinting and the evaluation of genetic diversity and population structure in international cowpea germplasm - Faheem Shehzad Baloch; Muhammad Tanveer Altaf; Mehmet Bedir; Muhammad Azhar Nadeem; Muhammed Tatar; Tolga Karaköy; Muhammad Aasim (Genetic Resources and Crop Evolution, 2023)

Artificial neural network and decision tree facilitated prediction and validation of cytokinin-auxin induced in vitro organogenesis of sorghum (Sorghum bicolor L.) - Muhammad Aasim; Seyid Amjad Ali; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shahzad Baloch (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exploring the genetic diversity and population structure of upland cotton germplasm by iPBS-retrotransposons markers - Nurettin Baran; Flavien Shimira; Muhammad Azhar nadeem; Muhammad Tanveer altaf; Mehtap andirman; Faheem Shehzad Baloch; Mefhar Gültekin Temiz (Molecular Biology Reports, 2023)

Elucidating the genetic variations among Turkish grape varieties using morphological and molecular markers - Ahmet Sümbül; Ercan Yildiz; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2023)

Assessing the genetic diversity in hawthorn (Crataegus spp.) genotypes using morphological, phytochemical and molecular markers - Ercan Yildiz; Ahmet Sümbül; Mehmet Yaman; Muhammad Azhar Nadeem; Ahmet Say; Faheem Shehzad Baloch; Gheorghe Cristian Popescu (Genetic Resources and Crop Evolution, 2023)

Light-emitting diodes induced in vitro regeneration of Alternanthera reineckii mini and validation via machine learning algorithms - Muhammad Aasim; Seyid Amjad Ali; Pınar Bekiş; Muhammad Azhar Nadeem (In Vitro Cellular & Developmental Biology - Plant, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Recent progress in omics and biotechnological approaches for improved mango cultivars in Pakistan - Ghassan Zahid; Yıldız Aka Kaçar; Flavien Shimira; Sara Iftikhar; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2022)

Assessment of genetic diversity among 131 safflower (Carthamus tinctorius L.) accessions using peroxidase gene polymorphism (POGP) markers - Mehtap Yildiz; Muhammad Tanveer Altaf; Faheem Shehzad Baloch; Metin Koçak; Gökhan Sadık; Cansu Kuzğun; Muhammad Azhar Nadeem; Fawad Ali; Mehmet Bedir; Murat Tunçtürk (Molecular Biology Reports, 2022)

Inoculation of Azospirillum brasilense and exogenous application of trans-zeatin riboside alleviates arsenic induced physiological damages in wheat (Triticum aestivum) - Muhammad Saqlain Zaheer; Hafiz Haider Ali; Kehinde O. Erinle; Shabir Hussain Wani; Okon Godwin Okon; Muhammad Azhar Nadeem; Muhammad Nawaz; Muhammad Adnan Bodlah; Muhammad Mohsin Waqas; Javaid Iqbal; Ali Raza (Environmental Science and Pollution Research, 2022)

Applicability of inter-primer binding site iPBS- retrotransposon marker system for the assessment of genetic diversity and population structure of Peruvian rosewood (Aniba rosaeodora Ducke) germplasm - Faheem Shehzad Baloch; Stalin Juan Vasquez Guizado; Muhammad Tanveer Altaf; Ilker Yüce; Yeter Çilesiz; Mehmet Bedir; Muhammad Azhar Nadeem; Rustu Hatipoglu; Juan Carlos Castro Gómez (Molecular Biology Reports, 2022)

Economic and financial impact of the COVID-19 pandemic in South Asia - Muhammad Azhar Khan; Hasnain Abbas Naqvi; Muhammad Mohsin Hakeem; Ghulam Moeen ud Din; Nadeem Iqbal (Environmental Science and Pollution Research, 2022)

Deciphering the genetic diversity and population structure of Turkish bread wheat germplasm using iPBS-retrotransposons markers - Muhammad Azhar Nadeem (Molecular Biology Reports, 2021)

Exploring the genetic diversity and population structure of scarlet eggplant germplasm from Rwanda through iPBS-retrotransposon markers - Flavien Shimira; Hatice Filiz Boyaci; Yeter Çilesiz; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Hatıra Taşkin (Molecular Biology Reports, 2021)

Genetic dissection of days to flowering via genome-wide association studies in Turkish common bean germplasm - Muhammad Azhar Nadeem; Ephrem Habyarimana; Tolga Karaköy; Faheem Shehzad Baloch (Physiology and Molecular Biology of Plants, 2021)

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Genome-wide association study identifies various loci underlying agronomic and morphological traits in diversified potato panel - Muhammad Abu Bakar Zia; Ufuk Demirel; Muhammad Azhar Nadeem; Mehmet Emin Çaliskan (Physiology and Molecular Biology of Plants, 2020)

Molecular characterization of genetic diversity and similarity centers of safflower accessions with ISSR markers - Fawad Ali; Muhammad Azhar Nadeem; Ephrem Habyarimana; Abdurrahim Yılmaz; Muhammad Amjad Nawaz; Iftikhar Hussain Khalil; Sezai Ercişli; Gyuhwa Chung; Hassan Javed Chaudhary; Faheem Shehzad Baloch (Brazilian Journal of Botany, 2020)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Food habits of the snow leopard Panthera uncia (Schreber, 1775) in Baltistan, Northern Pakistan - Muhammad Bilal Anwar; Rodney Jackson; Muhammad Sajid Nadeem; Jan E. Janečka; Shafqat Hussain; Mirza Azhar Beg; Ghulam Muhammad; Mazhar Qayyum (European Journal of Wildlife Research, 2011)